Cutthroat Island - Harlin, Renny; Davis, Geena; Modine, Matthew; Langella, Frank; Artisan Entertainment (Firm) (Van Nuys, Calif. : LIVE Entertainment, 1998)
Morgan Adams, the female captain of a pirate ship, is on a treasure hunt for millions of pounds of gold reportedly buried somewhere on Cutthroat Island. She and her uncles each hold sections of the map to the treasure. While Morgan is willing to make deals and agree to share the wealth in order to put the map together, her Uncle Dawg would rather kill everyone in his way, including his niece.
Originally released as a motion picture in 1995.
Length of time varies on container: 125 min. or 118 min. is listed.
Special features: Production notes; cast & crew bios; theatrical teaser and trailer.
Produced and directed by Renny Harlin; screenplay by Robert King and Marc Norman; music composed by John Debney.
Geena Davis, Matthew Modine, Frank Langella, Maury Chaykin, Patrick Malahide, Stan Shaw.
Rated PG-13.
Keywords: Pirates -- Drama; Swashbuckler films; Action and adventure films; Feature films